Scholarly communication and Research4Life: Research assessment and bibliometrics - Kabale University (Kabale University, 2023)
Become familiar with research impact and how it is evaluated, understand commonly used indicators and methodologies, understand alternative merits to journal-based metrics,recognize existing tools such as Google scholar, altmetrics, Scopus, Web of science, Dimensions, Scival, InCites and Lens